Edukasi tentang Shivering sebagai Komplikasi Anestesi dan Cara Penanganannya untuk Pasien dan Keluarga - Dwi Handoyo; Nita Yunianti Ratnasari; Heni Purwaningsih (FKIP, Universitas Palangka Raya, 2024)
Shivering is one of the complications that often occurs after anesthesia due to impaired body thermoregulation. This condition can cause discomfort, increase oxygen consumption, and prolong the patient's recovery period. Education about shivering is very important for patients and families so that they understand the causes, risks, and how to handle it. This education program is carried out using a counseling method that involves educational media in the form of leaflets and demonstrations of effective handling techniques, such as the use of warm blankets, giving warm fluids, and relaxation techniques. Evaluation is carried out by measuring the level of understanding of patients and families before and after education, through a prepared questionnaire. The evaluation results showed a significant increase in understanding about shivering and how to handle it, both in theory and practice. This increase shows that the education provided is effective in increasing the readiness of patients and families in dealing with post-anesthesia shivering. This program is expected to reduce the negative impact of shivering and accelerate the patient's recovery process.